Systematic Literature Review of Housing Policies in Carbon Emission Reduction: Reflection for Indonesia - Aswar Husen Buton; Nensi Golda Yuli; Ilya Fadjar Maharika (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2023)
Housing cannot be separated from the discourse of carbon emissions in all building cycles: planning and design, material preparation, construction, operations, and demolition. Various countries have successfully reduced carbon emissions in the housing sector, one of which is by using policy instruments. However, reviewing the effectiveness of these policies has yet to be thoroughly explored. Using the systematic literature review method, this article aims to identify the policies implemented to reduce carbon emissions in housing and contextualize them for Indonesia. After careful identification of the relevant articles, 16 selected articles were reviewed. The study found that taxation, zero-carbonization, and strategies for retrofitting are adequate policies in many countries. Framework for Indonesia was discussed for recommendations.